(untitled) (Bioscience Journal, 2018)
The objectives of this study were to evaluate the serum biochemical profile in Quarter Horse mares in their peripartum, and neonates on their birth date, and to compare the values obtained for male and female foals, as well as values obtained for foals and mares on the day of delivery. Forty one adult, pregnant mares and their respective offspring on the day of delivery were analyzed, totaling 82 animals. Two samples of blood were collected from the mares, seven days before and on the day of delivery. From the foals, blood collection was performed on the day of their birth about 12 h after colostrum ingestion. The samples were centrifuged and the serum stored at -20 ºC for analyses. Each sample was used to determine the serum concentrations proteins, metabolites, minerals and enzymes. Physiological changes caused by peripartum led to higher serum total protein, albumin, and globulins on the day of delivery. Serum concentration of triglycerides and calcium /phosphorus ratio were greater seven days before delivery; iron concentration was higher than reference ranges in both moments of evaluation. In foals, albumin serum concentrations, albumin/globulins ratio, and aspartate aminotransferase remained below reference ranges. In foals, there was no influence of sex in the serum biochemical profile. When results obtained for foals on their birth date were compared with those obtained for the mares on the delivery day, cholesterol, triglycerides, phosphorus, iron, alkaline phosphatase, and gamma glutamyltransferase were higher in foals, and total protein, albumin, globulins, urea nitrogen, calcium/phosphorus ratio, and aspartate aminotransferase were higher in mares. Results showed variations in serum biochemistry in peripartum mares and neonates, as well as in the comparison between foals and mares on the day of delivery. Clinically, serum biochemistry values for peripartum mares and neonates should be considered in the analysis of laboratory results of tests carried out in this period.